2022
DOI: 10.1186/s12913-022-07877-8
|View full text |Cite
|
Sign up to set email alerts
|

Measuring treatment attrition at various stages of engagement in Opioid Agonist Treatment in Ontario Canada using a cascade of care framework

Abstract: Background The cascade of care framework is an effective way to measure attrition at various stages of engagement in Opioid Agonist Treatment (OAT). The primary objective of the study was to describe the cascade of care for patients who have accessed OAT from a network of specialized addiction clinics in Ontario, Canada. The secondary objectives were to evaluate correlates associated with retention in OAT at various stages and the impact of patients’ location of the residence on retention in OA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 51 publications
3
7
0
Order By: Relevance
“…Retention in treatment has been associated with an increased abstinence from non-treatment opioids. 49 Consistent with this, retention at visit 12 (i.e., week 24) in the methadone arm was associated with a higher incidence of having a non-treatment OFUS; moreover, the OPRM1 rs1799971 G-genotypes were associated with lower retention compared with the AA genotype (Table S6). The OPRM1 rs1799971 G-genotypes were also associated with lower odds of having a non-treatment OFUS when retained at visit 12, compared with the AA genotype, suggesting that the poorer treatment success on methadone observed among those with Ggenotypes may be due, in part, to reduced retention in methadone treatment (Table S6).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Retention in treatment has been associated with an increased abstinence from non-treatment opioids. 49 Consistent with this, retention at visit 12 (i.e., week 24) in the methadone arm was associated with a higher incidence of having a non-treatment OFUS; moreover, the OPRM1 rs1799971 G-genotypes were associated with lower retention compared with the AA genotype (Table S6). The OPRM1 rs1799971 G-genotypes were also associated with lower odds of having a non-treatment OFUS when retained at visit 12, compared with the AA genotype, suggesting that the poorer treatment success on methadone observed among those with Ggenotypes may be due, in part, to reduced retention in methadone treatment (Table S6).…”
Section: Discussionsupporting
confidence: 59%
“…Retention in treatment has been associated with an increased abstinence from non‐treatment opioids 49 . Consistent with this, retention at visit 12 (i.e., week 24) in the methadone arm was associated with a higher incidence of having a non‐treatment OFUS; moreover, the OPRM1 rs1799971 G‐genotypes were associated with lower retention compared with the AA genotype ( Table ).…”
Section: Discussionsupporting
confidence: 54%
“…While the use of these medications is useful for many people who use drugs (PWUD), retention rates in care remain low. A recent study in Ontario, Canada, found that from 2014 to 2020, 58% of patients receiving OAT were not retained in treatment beyond 2 years-in fact, nearly 20% were retained for less than 90 days [14]. A randomized controlled trial in British Columbia, Canada, compared the use of injectable diacetylmorphine and oral methadone treatment for individuals who injected opioids daily.…”
Section: Introductionmentioning
confidence: 99%
“…Since 2017, CATC cohort data have resulted in a total of 16 publications5 25–38 and has provided valuable clinical insights.…”
Section: Findings To Datementioning
confidence: 99%
“…Additionally, patients were 1.149 times more likely to drop out of treatment if they had benzodiazepine-positive urine samples (adjusted HR (aHR) 1.149, 95% CI 1.02 to 1.29)30; OAT patients with baseline cannabis use and heavy cannabis use were at increased risk of dropout (1.39 and 1.48 times more likely, respectively)31; compared with those with no amphetamine-type stimulant use, the number of days retained in OAT treatment for people who use amphetamine-type stimulant was reduced (aHR 1.19, 95% CI 1.07 to 1.17)34 and people who used cocaine at baseline were 1.24 times more likely to drop out of treatment than baseline non-users (aHR 1.124, 95% CI 1.03 to 1.23) 32. Furthermore, our previous studies highlighted several factors associated with patients’ retention in treatment including the number of prior treatment attempts, a higher frequency of average monthly UDS and a lower proportion of positive UDS results for substances other than opioids 35 36…”
Section: Findings To Datementioning
confidence: 99%